Development of a neuroprotective potential algorithm for medicinal plants. (November 2016) - Liu, Weixi; Ma, Hang; DaSilva, Nicholas A.; Rose, Kenneth N.; Johnson, Shelby L.; Zhang, Lu; Wan, Chunpeng; Dain, Joel A.; Seeram, Navindra P.
Abstract: Medicinal plants are promising candidates for Alzheimer's disease (AD) research but there is lack of systematic algorithms and procedures to guide their selection and evaluation. Herein, we developed a Neuroprotective Potential Algorithm (NPA) by evaluating twenty-three standardized and chemically characterized Ayurvedic medicinal plant extracts in a panel of bioassays targeting oxidative stress, carbonyl stress, protein glycation, amyloid beta (Aβ) fibrillation, acetylcholinesterase (AChE) inhibition, and neuroinflammation. The twenty-three herbal extracts were initially evaluated for: 1) total polyphenol content (Folin-Ciocalteu assay), 2) free radical scavenging capacity (DPPH assay), 3) ferric reducing antioxidant power (FRAP assay), 4) reactive carbonyl species scavenging capacity (methylglyoxal trapping assay), 5) anti-glycative effects (BSA-fructose, and BSA-methylglyoxal assays) and, 6) anti-Aβ fibrillation effects (thioflavin-T assay). Based on assigned index scores from the initial screening, twelve extracts with a cumulative NPA score ≥40 were selected for further evaluation for their: 1) inhibitory effects on AChE activity, 2) in vitro anti-inflammatory effects on murine BV-2 microglial cells (Griess assay measuring levels of lipopolysaccharide-induced nitric oxide species), and 3) in vivo neuroprotective effects on Caenorhabditis elegans post induction of Aβ1-42 induced neurotoxicity and paralysis. Among these, four extracts had a cumulative NPA score ≥60 including Phyllanthus emblica (amla; Indian gooseberry), Mucuna pruriens (velvet bean), Punica granatum (pomegranate) and Curcuma longa (turmeric; curcumin). These extracts also showed protective effects on H2 O2 induced cytotoxicity in differentiated cholinergic human neuronal SH-SY5Y and murine BV-2 microglial cells and reduced tau protein levels in the SH-SY5Y neuronal cells. While published animal data support the neuroprotective effects of several of these Ayurvedic medicinal plant extracts, some remain unexplored for their anti-AD potential. Therefore, the NPA may be utilized, in part, as a strategy to help guide the selection of promising medicinal plant candidates for future AD-based research using animal models. Graphical abstract: Highlights: Twenty-three medicinal plant extracts were evaluated for neuroprotective effects. A neuroprotective potential algorithm (NPA) was developed. Top candidates show neuroprotective effects in vitro and in Caenorhabditis elegans . Top candidates have published animal data to support their neuroprotective effects. NPA may be used to aid in selecting botanicals for further in vivo studies.